Fragmentation, feuilleton, form: Balzac, Baudelaire, Zola. (2nd October 2017) - Farrant, Tim
ABSTRACT: Beginning with Baudelaire's preface to the Petits poèmes en prose, and spanning writers from early Dumas, Stendhal, Sand and Hugo to Zola, this article asks whether serialized fragmentation was quite the virtue Baudelaire's preface makes it, or more a double-edged commercial necessity. Raising Nodier's and Mérimée's querying of unity, it explores the questions of form, narrative and moral, that Balzac's La Vieille Fille presents, and traces the retreat from ethically (especially sexually) dangerous territory in Balzac's and Delphine de Girardin's contemporary and subsequent serialized texts. Hugo's Le Dernier Jour d'un condamné and Les Misérables are offered as counter-examples of fictions which were not serialized, perhaps because more thematically and formally unified than the feuilleton narratives discussed, and because, unlike them, they ask a more challenging, primarily moral rather than narrative question: not What? or How? but Why? A closing reflection on Zola indicates how journalistic serialization disseminated and made the novel as a popular, increasingly solipsistic genre, yet, in its dependence on money, almost destroyed the form.